THE EFFECT OF TELENURSING IMPLEMENTATION ON THE QUALITY OF LIFE (QoL) OF PATIENTS WITH CHRONIC DISEASES: A SYSTEMATIC REVIEW - FADHILAH, NUUR (Nurse and Health: Jurnal Keperawatan, 2025)
Background:There are still differences in access to health services in Indonesia in the current digital era because conditions show that rural residents, especially those living in border areas, experience obstacles in obtaining health services and the prevalence of chronic diseases has increased, with hypertension rising from 25.8% to 34.1%, diabetes mellitus rising from 6.9% to 8.5%, stroke prevalence rising from 7% to 10.9%, and chronic kidney disease rising from 2% to 3.8%. Purpose:The purpose  is to determine the effect of telenursing implementation on the quality of life of patients with chronic diseases. Methods:The method applied is a systematic review referring to the PRISMA guidelines, articles for the last 5 years, subject area, nursing, relevance, article types, and were selected to be analyzed and assessed using JBI. Results:The research findings indicate that nine studies were taken from 1,373 publications. Publications were taken from the period 2021 to 2025. Research articles were searched through academic electronic databases (Scopus, Pubmed, and Google Scholar). The implementation of telenursing has positive implications for the quality of life of patients with chronic diseases. Conclusion:Telenursing  has shown positive results in improving  the hope of improving the quality of life of patients with chronic illnesses. The variety of media and applications used in the implementation of telenursing also contributes to its success. It is hoped that further research will further examine the factors influencing the implementation of telenursing and  also research can be conducted on the same media.